Analysis of Potential Damage to Hydrotester Machines Using FMEA and FTA Methods at PT. ISP to Improve Maintenance Reliability - Johan Wiranaka; Deny Andesta; Efta Dhartikasari (G-Tech: Jurnal Teknologi Terapan, 2025)
PT. Indal Steel Pipe (ISP) is a steel pipe manufacturing company that relies on hydrotester machines as an essential tool to ensure product quality. The high production volume and intensive use of machinery have led to frequent failures, such as water hose leakage, rubber seal damage, and electrical system failure. These issues led to unplanned downtime of up to 3.09% of total operating time and 400 minutes of repairs in the last six months, which reduced productivity. This study aims to identify the hydrotester components with the highest risk of failure and establish maintenance priorities. The methods applied are Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). FMEA is used to calculate the Risk Priority Number (RPN) based on severity, frequency, and detection, while FTA helps to systematically trace the root cause of failure. The results showed that the broken pipe rubber had an RPN value of 245, followed by a leaky hydrolis with an RPN of 180, followed by a leaking water pipe hose with an RPN value of 168. Further FTA analysis identified material wear and excessive operational stress as the dominant causes of failure. These findings highlight that combining FMEA and FTA provides an effective approach in formulating maintenance strategies, thereby minimizing risk, reducing downtime, and ensuring production continuity. The novelty of this study lies in integrating FMEA and FTA to prioritize maintenance actions specifically for hydrotester machines, offering practical guidelines for industries with similar equipment.